2016
DOI: 10.1182/blood-2016-01-694604
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase 2 study: elotuzumab plus bortezomib/dexamethasone vs bortezomib/dexamethasone for relapsed/refractory MM

Abstract: Key Points• Elotuzumab, an immunostimulatory antibody, prolongs PFS with no added clinical toxicity when combined with Bd vs Bd alone in RRMM.• Based on results from this phase 2 study, further investigation of elotuzumab with a proteasome inhibitor in RRMM is warranted.In this proof-of-concept, open-label, phase 2 study, patients with relapsed/refractory multiple myeloma (RRMM) received elotuzumab with bortezomib and dexamethasone (EBd) or bortezomib and dexamethasone (Bd) until disease progression/unacceptab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
146
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(152 citation statements)
references
References 23 publications
2
146
0
4
Order By: Relevance
“…158 In both examples, the ability of a specific agent (e.g., oxaliplatin, cyclophosphamide) but not one of its alike (e.g., cisplatin, melphalan) to drive ICD can be explained by the differential activation of ER stress (and hence differential exposure of CALR in the course of RCD). 100,[157][158][159] Well established ICD inducers include commonly employed anticancer chemotherapeutics such as: (1) (6) bortezomib, a proteasomal inhibitor approved for the therapy MM and mantle cell lymphoma (MCL); [171][172][173][174][175][176][177][178][179][180][181] (7) cyclophosphamide, a DNA-alkylating agent approved for use in patients with chronic myeloid leukemia (CML), AML, ALL, chronic lymphocytic leukemia, MM, ovarian carcinoma, breast carcinoma, mycosis fungoides, lymphoma, neuroblastoma, and retinoblastoma; 177,[182][183][184][185][186][187][188][189][190][191] and (8) oxaliplatin, a platinum-derivative licensed for the therapy of advanced colorectal carcinoma in combination with 5-fluorouracil and folinic acid. 156,157,[192][193][194][195][196][197][198] Moreover, there is some evidence that microtubule-targeting agents including taxanes and vinca alkaloids (which are commonly used for the treatment of multiple carcinomas) can stimulate ICD.…”
Section: Introductionmentioning
confidence: 99%
“…158 In both examples, the ability of a specific agent (e.g., oxaliplatin, cyclophosphamide) but not one of its alike (e.g., cisplatin, melphalan) to drive ICD can be explained by the differential activation of ER stress (and hence differential exposure of CALR in the course of RCD). 100,[157][158][159] Well established ICD inducers include commonly employed anticancer chemotherapeutics such as: (1) (6) bortezomib, a proteasomal inhibitor approved for the therapy MM and mantle cell lymphoma (MCL); [171][172][173][174][175][176][177][178][179][180][181] (7) cyclophosphamide, a DNA-alkylating agent approved for use in patients with chronic myeloid leukemia (CML), AML, ALL, chronic lymphocytic leukemia, MM, ovarian carcinoma, breast carcinoma, mycosis fungoides, lymphoma, neuroblastoma, and retinoblastoma; 177,[182][183][184][185][186][187][188][189][190][191] and (8) oxaliplatin, a platinum-derivative licensed for the therapy of advanced colorectal carcinoma in combination with 5-fluorouracil and folinic acid. 156,157,[192][193][194][195][196][197][198] Moreover, there is some evidence that microtubule-targeting agents including taxanes and vinca alkaloids (which are commonly used for the treatment of multiple carcinomas) can stimulate ICD.…”
Section: Introductionmentioning
confidence: 99%
“…If an infusion reaction (IR) did not occur, the infusion rate could be increased to 5 mL/min (duration 1 h) after Cycle 4. 19,20 In study 1703, patients with RRMM receiving elotuzumab plus lenalidomide and dexamethasone demonstrated an overall response rate (ORR) of 84% and a median progression-free survival of 28.6 months. 19 The most common Grade 3/4 adverse events (AEs) were lymphopenia (21%) and neutropenia (19%).…”
Section: Introductionmentioning
confidence: 99%
“…One IR was reported among the 27 patients who had received the 5 mL/min infusion. 20 The premedication regimen and administration schedule of these medications implemented in studies 1703 and 009 were shown to successfully reduce the number and severity of IRs associated with elotuzumab. 19,22 As a result, this premedication regimen, or an appropriate equivalent, is currently required for all patients prior to infusion of elotuzumab.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As single agent in RRMM patients, no objective responses were observed (Table 2) [13], and a potential role in combination with other MM agents was hypothesized. Recently, elotuzumab in combination with bortezomib-dexamethasone (VD; ELO-VD) induced an ORR of 66% and a median PFS approximately 3 months longer than the one reported with VD alone [14]. No additional clinically significant adverse events occurred with ELO-VD versus VD.…”
mentioning
confidence: 99%